Long-Term Efficacy and Complications of Radiofrequency Thermocoagulation at Different Temperatures for the Treatment of Trigeminal Neuralgia. (5th March 2020) - Hong, Tao; Ding, Yuanyuan; Yao, Peng
Abstract : Trigeminal neuralgia (TN) is a common neuropathic pain that seriously affects the daily life of patients. Many invasive treatments are currently available for patients who respond poorly to oral carbamazepine or oxcarbazepine. Among them, radiofrequency (RF) treatment is a viable option with reliable initial and long-term clinical efficacy. The long-term analgesic effects of radiofrequency thermocoagulation (RFT) at high temperatures (≥80°C) are not superior to those at relatively low temperatures (60–75°C). In contrast, the higher the temperature, the greater the risk of complications, especially facial numbness, masticatory muscles weakness, and corneal hypoesthesia. Some patients even experience irreversible lethal complications. Therefore, we recommend low-temperature RFT (60–75°C) for treatment of TN. The therapeutic effects of pulsed radiofrequency (PRF) are controversial, whereas PRF (≤75°C) combined with RFT can improve long-term effects and decrease the incidence of complications. However, large-scale clinical trials are needed to verify the efficacy of the combination of PRF and RFT.